2007
DOI: 10.1007/s11104-007-9332-3
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining productivity of wheat–soybean cropping system through integrated nutrient management practices on the Vertisols of central India

Abstract: Wheat-soybean is one of the most dominant cropping systems on the Vertisols of central India. Cultivation of durum wheat in winter season (November to April) has a considerable potential due to congenial climate, while soybean in rainy season (June to October) has witnessed a phenomenal growth in the last two decades in the region. Beside including a legume (soybean) in sequence with a cereal crop (wheat), combined use of available organic sources along with chemical fertilizers may prove beneficial for long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 8 publications
(6 reference statements)
5
52
1
Order By: Relevance
“…For instance, application of 30:26:25% kg ha -1 NPK + 4000 kg ha -1 manure in India effectively yielded higher soybean productivity (Bandyopadhyay et al 2010), meanwhile other studied reported that application of 2500 kg ha -1 poultry manure significantly improved soybean yield and seed quality (Behera et al 2007). The difference dosage effect of manure on every plant cultivated actually was affected by the nutrient content of manure and the soil.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, application of 30:26:25% kg ha -1 NPK + 4000 kg ha -1 manure in India effectively yielded higher soybean productivity (Bandyopadhyay et al 2010), meanwhile other studied reported that application of 2500 kg ha -1 poultry manure significantly improved soybean yield and seed quality (Behera et al 2007). The difference dosage effect of manure on every plant cultivated actually was affected by the nutrient content of manure and the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Subba Rao et al, 1998 andBehera et al, 2007 reported similar result. Control-NPK(00-00-00) Control-NPK(00-00-00) T 2 RDF -NPK (120-60-60) ha Table.2 Effect of organic and inorganic source of plant nutrients application on Yield, REY, system productivity, profitability and economics of rice -wheat cropping system This was evidently due to addition of organic matter containing major and micronutrients, as well as their solubilizing effect on native nutrients (Manna et al, 2003 andBehera et al, 2007). Thus, it may be concluded that conjoint application of organic and inorganic sources of nutrients enhanced yield and improved soil fertility.…”
Section: Soil Fertilitymentioning
confidence: 59%
“…The soil available P increased by 62, 45 and 36% for treatments T 4 , T 5 and T 6 , respectively over the control (T 1 ), it was reported that organic manuring as sludge, vermicompost and sesbania played a beneficial role in retaining a major portion of the added P in plant available form by suppressing P sorption (Iyamuremye and Dick 1996) and improving soil P fertility status (Reddy et al, 1999 andBehera et al, 2007). Significantly higher concentration of available P in customized fertilizer might be attributed to its higher rate of addition.…”
Section: Soil Fertilitymentioning
confidence: 99%
“…Also an understanding of the dynamics of carbon (C) stock in soils, as impacted by management strategies, is necessary to identify the pathways of C sequestration in soils and for maintaining soil organic C (SOC) at a level critical for up keeping soil health and also for restraining global warming (Bastia et al, 2013, Bonilla et al, 2012. Therefore, fractionating and quantifying the labile and recalcitrant C pools could provide valuable information for better understanding SOC changes and the underlying mechanisms (Behera et al, 2007). Long-term fertilizer experiments showed that applying chemical fertilizer in combination with farmyard manure significantly increased SOC content more than using chemical fertilizer alone in tropical cropping system (Lima et al, 2009) and semi-arid tropics (Banger et al, 2009).…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 487-496mentioning
confidence: 99%
“…The maximum microbial growth in organic treated plots was due to the presence of easily water soluble C and N in FYM (Paul et al, 2003), which acts as a source of energy for soil organisms, whereas the easily soluble C component was missing in mineral fertilizer (Behera et al, 2007) and, hence, the microbial population was less in the plots under NPK. The current findings are in the agreement with results obtained by (Bonilla et al, 2012, Zhang et al, 2012.…”
Section: Soil Propertiesmentioning
confidence: 99%